Pensionsinvesteringer, etik og offentlighed: En systemteoretisk analyse af offentlig meningsdannelse - Steen Vallentin (Copenhagen Business School (CBS), 2002)
[...]"the thesis tries to show how – with the appearance of the themes ethics and democracy – new conditions have evolved for the administration of the Danish pension fund investments. It should be emphasized that the thesis not only aims to provide a description of the Danish debate about ethical investments; it makes a separate contribution to systems theory. This contribution consists in a general presentation of Luhmann's theory (chapter 2) followed by discussions of Luhmann's concepts of risk (chapter 3), morality and ethics (chapter 4) and public and public opinion (chapter 5). In theoretical terms the contribution of the thesis lies in showing how Luhmann's systems theory can be used to describe and analyze public opinion formation in general and the debate about the Danish pension fund investments in particular. The thesis focuses on Danish developments but international developments are not ignored. To put Danish developments into perspective, a part of chapter 1 focuses on developments surrounding ethical – or socially responsible – investments in the US and the UK. Matters of definition, historical developments and praxis forms are presented and lead up to an overview of key events in the domestic debate. It is argued that the Danish debate – unlike the very individualistic anglo-saxon debate – has focused on collective matters. The debate has focused on institutions which make investment decisions on behalf of many – often hundreds of thousands of – people, institutions which do not operate in a free market setting. A brief description of Danish developments is followed by a summary of and further reflexions upon the analytical arguments of the thesis.
hdl:10398/7131
Keywords: 650; offentlig meningsdannelse; diskursanalyse; pensionskasseinvesteringer; virksomhedsetik; kommunikationsteori; sociologisk systemteori; sociologisk teori; etiske investeringer